Associations Between Cortisol Stress Levels and Autism Symptoms in People With Sensory and Intellectual Disabilities - de Vaan, Gitta; Beijers, Roseriet; Vervloed, Mathijs P. J.; Knoors, Harry; Bloeming-Wolbrink, Kitty A.; de Weerth, Carolina; Verhoeven, Ludo (Frontiers in Education, 2020)
Background and aims Individuals with combined sensory and intellectual disabilities are more sensitive to stress than people without disabilities, especially when they have an Autism Spectrum Disorder (ASD). Reversely, stress can also trigger ASD symptoms. The current study investigated the relationship between stress and ASD symptoms in this population. Methods and Procedures Participants (n=46) were individuals with combined sensory and intellectual disabilities. The presence of ASD was assessed with Observation of Autism in people with Sensory and Intellectual Disabilities (OASID). This assessment also served as a stressor. Stress levels were measured with salivary cortisol during the OASID assessment and on a control day. Results There were no differences in cortisol levels between participants with and without ASD, or between the OASID test day and control day. Half the study sample showed high cortisol levels compared to a reference group. Cortisol levels were positively related to the presence of stereotyped and repetitive behaviors. Conclusions No differences were found in stress levels after administration of OASID between people with or without ASD based on the classification of OASID. Administration of OASID was found not to produce increases in cortisol. Cortisol levels were correlated with stereotyped and repetitive behaviors, which makes it likely that these behaviors are stress reactions.